Low-frequency, low-intensity ultrasound accelerates thrombolysis through the skull - Behrens, Stephan; Daffertshofer, Michael; Spiegel, Dagmar; Hennerici, Michael G. (Ultrasound in medicine & biology, 1999)
Systemic thrombolysis of acute ischemic stroke with recombinant tissue plasminogen activator (rt-PA) has been established recently. Whereas the delay to and the rate of vessel recanalization are unknown, they are likely slower and smaller than for local application of rt-PA. This may contribute to the small benefits of recovery reported and stimulate further investigations to improve clot lysis. Pilot studies indicate that continuous-wave low-frequency ultrasound (US) can accelerate rt-PA-mediated recanalization of peripheral thrombotic vessel occlusion. For the hypothesized therapeutical purpose in stroke treatment, we measured the attenuation of ultrasound through the skull at different frequencies and intensities (33.3 and 71.4 kHz; 0.5 and 3.4 W/cm2), and investigated thrombolysis in vitro (n = 125 clots). Attenuation was lowest by transtemporal insonation of 33.3 kHz, 0.1 dB (0.9). Thrombolysis (artificial fibrin-rich clots) was significantly increased after 1 h (p < 0.025) and after 3 h (p < 0.01) for US treatment in combination with rt-PA vs. rt-PA alone. Results suggest that US increases rt-PA-mediated thrombolysis through the skull and may improve benefits of thrombolytic stroke treatment in vivo.
Gesehen am 27.07.2022